Unicentric hyaline vascular Castleman’s disease presenting as an intraparenchymal parotid mass: a rare case report - Dandala, Sridhar R.; Gonuru, Vinod K.; Dola, Manoranjani (International Journal of Research in Medical Sciences, 2025)
Castleman’s disease (CD) is a rare, benign lymphoproliferative disorder of unknown etiology that can affect any lymph node group, with the mediastinum being the most common site. Salivary gland involvement is exceptionally rare. We present a case of a 30-year-old female with a slowly progressive, painless left-sided parotid swelling persisting for four months. Clinical examination, ultrasonography and fine-needle aspiration cytology (FNAC) initially suggested an intraparotid lymph node enlargement. The lesion was excised and histopathological examination confirmed hyaline vascular CD. Given its rarity and lack of specific clinical or radiological features, CD should be considered in the differential diagnosis of persistent parotid gland swellings. Surgical excision remains the mainstay of treatment for unicentric Castleman’s disease (UCD) with an excellent prognosis.